2003
DOI: 10.1152/jn.00343.2003
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Attention and Detection Signals During Visual Search

Abstract: Prior work has distinguished regions in the intraparietal sulcus (IPs) and frontal eye field (FEF) involved in the voluntary control of attention, from more ventral regions in the temporoparietal junction (TPJ) involved in target detection. The present results show that when subjects search for and detect a visual target stimulus among nontargets, these regions show sensory-, search-, and detection-related signals that both confirm and refine these functional distinctions. The different signals were isolated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
217
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 233 publications
(272 citation statements)
references
References 73 publications
(78 reference statements)
46
217
3
1
Order By: Relevance
“…Observers with stronger negative correlation between visual cortex and default mode regions at baseline may find it easier to filter out distracters at unattended locations early in training, which becomes less important as target selection becomes more automatic. This interpretation is consistent with a role of the default mode network in filtering out unattended stimuli, as suggested by other studies (39)(40)(41). Behaviorally significant negative correlations in FC between visual cortex and default mode regions have also been reported in relation to reading skills in children and adults, a competency closely related to orientation discrimination (25).…”
Section: Discussionsupporting
confidence: 91%
“…Observers with stronger negative correlation between visual cortex and default mode regions at baseline may find it easier to filter out distracters at unattended locations early in training, which becomes less important as target selection becomes more automatic. This interpretation is consistent with a role of the default mode network in filtering out unattended stimuli, as suggested by other studies (39)(40)(41). Behaviorally significant negative correlations in FC between visual cortex and default mode regions have also been reported in relation to reading skills in children and adults, a competency closely related to orientation discrimination (25).…”
Section: Discussionsupporting
confidence: 91%
“…That is, during memory-guided decision-making under uncertainty (indexed by long RTs), top-down attention processes in SPL are highly engaged, and bottom-up attention processes in TPJ are suppressed. In this context, the current results parallel findings in the attention literature that suggest a deactivation of ventral PPC during demanding visuospatial tasks (Shulman et al 2003;Todd et al 2005;Shulman et al 2007), and formal meta-analysis revealed that the left TPJ region identified in the present study anatomically overlaps with the left parietal component of the ventral, bottom-up attention network proposed by Corbetta and Shulman (2002) (Fig. 6e).…”
Section: Dorsal Ppc: Lateral Ips Versus Splsupporting
confidence: 89%
“…On the other hand, the locations of these ROIs and their activity profiles are broadly compatible with effects stemming from graded differences in the engagement of top-down attention during retrieval. First, both regions roughly overlap with the dorsal frontal-parietal top-down attention network (e.g., Shulman et al (2003) reported MNI . Second, the direction of activation (Task > Specific Source) mirrored the corresponding condition-level differences in RT, as Task Source trials were associated with RTs that were on average 335 ms slower than those on Specific Source trials (Fig.…”
Section: Graded Memory Experimentsmentioning
confidence: 99%
“…Before electrode implantation, resting-state fMRI scans were obtained, allowing us to identify both the DAN and VAN in each subject using standard functional connectivity analyses. Similar analyses identified a sensorimotor network (SMN), which prepares and executes the subjects' response to the target, and a default-mode network (DMN) in which activity is either unchanged or suppressed during performance of visual attention tasks (18,19). The ECoG electrodes were spatially registered with the fMRI data, allowing us to assign specific electrodes to each of the four networks (see Experimental Procedures and SI Experimental Procedures for further details).…”
Section: Significancementioning
confidence: 99%